PEMBUATAN PETA SITUASI LOKASI 1 DUKUH CUNGKRUNGAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , RENDY SETIAWAN, Ir. Christine Noegroho Kartini, SU.Pj. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project explain about measurement and mapping of land to produce spatial data information from the Earth's surface. Spatial data includes detailed information planimetric and high points obtained from measurements of the Earth's surface and are presented in the form of a map. The method used in the making of map is the manufacture of map control framework that includes measuring the horizontal control framework and vertical control framework, planimetric detail and spot high measurements, and also digital mapping. The results obtained is the situation map presenting the information spatial data on the earth's surface area of location 1, Cungkrungan hamlet, Banyuripan village, Bayat sub-district, Klaten district, Central Java province by using a scale of 1: 500 in UTM projection system (Universal Transverse Mercator).